How and when do we use continuous renal replacement therapy for acute kidney injury in Serbia? – The multicentric survey - Knežević, Violeta; Ćelić, Dejan; Azaševac, Tijana; Golubović, Sonja; Sladojević, Vesna; Nestorov, Nataša; Maksić, Djoko; Naumović, Radomir; Lazarević, Tatjana; Nešković, Vojislava (Vojnosanitetski pregled, 2022)
Background/Aim. The absence of clear guidance in the definition, diagnostics, and indications for renal replacement treatment (RRT) is present. The aim of this study was to help outlining future clinical work in improving the treatment outcome and reducing complications of acute kidney injury (AKI) based on the current clinical practice. Methods. The questionnaires were distributed among physicians of different specialties who participated voluntarily and anonymously. The questionnaire was drawn up in accordance with the standard clinical practice. Results. We conducted a multicentric web survey among nephrologists (46.8%) and other physicians in Serbia. The sample consisted of 119 participants, out of which 78.9% filled out the survey forms correctly and were, therefore, included in the analysis. Most of them responded that the nephrologist indicates (76.8%) and prescribes (74.5%) continuous renal replacement therapy (CRRT). The application of the Kidney Disease Improving Global Outcomes (KDIGO) 2 criterion for “early” start of CRRT used 74.5% of the respondents, and 91.5% of them started “late” initiation of CRRT in the presence of complications associated with AKI or poor response to conservative treatment. Regarding the clinical experience of the respondents, 74.5% of them marked the “early” start of CRRT within 12 hours, whereas 56.4% of them considered the start of CRRT after 48 h as “late”. The most commonly used modality was continuous venous hemodiafiltration (37.6%). Most participants used heparin as an anticoagulant (95.7%) with an average life span of filters less than 24 h (71.3%) and 25 mL/kg/h efficiency target dialysis effluent dose (45.2%) during CRRT. The most common complications of CRRT were hypotension (55.3%) and catheter-related infections (29.8%). Conclusion. The “early” start of CRRT is considered favorite by the majority of the participants. According to the obtained data, standardization of the strategy in the diagnostics and treatment of AKI is necessary.